Learning Videos Based on Contextual Approaches to the Content of Pancasila and Citizenship Education - Theresa Afriani Cantum Pel; I Made Tegeh; I Komang Sudarma (Universitas Pendidikan Ganesha, 2023)
The lack of media use in the learning process impacts the low learning outcomes of students' Civics. This research aims to create contextual-based learning videos to improve student Internship learning outcomes. This research belongs to the type of development research that was developed by applying the ADDIE development model. The subjects in this study were educational technology experts, subject content experts, instructional design experts, learning media experts, and 12 grade VI elementary school students. Data collection in the study was carried out using the questionnaire/questionnaire and test method, with research instruments in questionnaires/questionnaire sheets and students' Civics ability tests. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques and t-test inferential statistics. The research analysis results showed that in the educational technology expert test. The developed media obtained a score of 95% with very good qualifications. The subject content expert test obtained a score of 90% with very good qualifications. The learning design expert test obtained a score of 90% with very good qualifications. The learning media expert test obtained a score of 92.5% with very good qualifications. Furthermore, the t-count analysis results show significant differences in student learning outcomes before and after using learning videos. Based on the results of this analysis, learning video media based on a contextual approach is valid and appropriate for use in learning because it can improve students' Civics learning outcomes.